John Locke and the Toleration of Catholics: A New Manuscript - Walmsley, J. C. (The historical journal, 2019)
The following Communication presents a newly discovered manuscript by John Locke. The manuscript dates from 1667–8 and it deserves notice as the most significant example of Locke's thought on the toleration of Catholics prior to the Epistola de tolerantia (1689). The manuscript, entitled Reasons for tolerateing Papists equally with others, reveals Locke's engagement with Sir Charles Wolseley's Liberty of conscience, the magistrates interest (1668) and significantly informs the compositional history of Locke's Essay concerning toleration (1667–8).